The moderating influence of socio‐demographic factors on the relationship between consumer psychographics and the attitude towards private label brands. Issue 6 (17th October 2013) - Shukla, Paurav; Banerjee, Madhumita; Adidam, Phani Tej
Abstract This study examines the moderating influence of socio‐demographic variables (gender, age, education, income and family size) on the relationship between psychographic measures (general deal proneness, price‐related deal proneness, end‐of‐aisle display proneness, impulsiveness, smart‐shopper self‐perceptions and brand loyalty) and consumers' attitude towards private label brands. The proposed hypotheses are tested by collecting data at three different British supermarkets and assessed using structural equation modelling. The study reveals findings contrary to the prevailing views about consumer psychographics and socio‐demographics, including the following: (i) the significance of deal proneness among high‐income consumers; (ii) the end‐of‐aisle display proneness among older, high‐income and highly educated consumers; and (c) the relationship between impulsiveness and brand attitude among low‐income and less‐educated consumers. The study also provides multiple insights relating to psycho‐demographic targeting and display strategies. Copyright © 2013 John Wiley & Sons, Ltd.